INTER• RELIGIOUS DIALOGUE AS A POLITICAL QUEST : . - Wilfred, Felix (Journal of Dharma, 2002)
Inter-religious dialogue is today an ethical imperative. Any religious tradition which cares for the well being of the society cannot fail to realize the crucial importance of harmony and understanding among the religious groups in India. The dialogue has been taking place mainly at two levels: At the first level, which can also be called the formal level, there has been sharing and exchange in matters of doctrines, world-views and the ideals the various religious traditions propose, and the experience to which each religion leads its followers. At the second level, which can be called the informal level, we have the dialogue of life, by which is meant the good-will and understanding fostered in day-to-day life among the believers of various religious traditions.